A Convenient Catalytic Procedure for Direct Synthesis of Arylselanyl Anilines - Yu, Chen; Shi, Hongwei; Zhu, Min; Yan, Jie (Synlett, 2015)
In the presence of a catalytic amount of KI combined with oxidant H2O2, a convenient catalytic procedure has been developed for the direct preparation of arylselanyl anilines from N,N-disubstituted anilines and diselenides. In this protocol, KI is first oxidized by H2O2 into hypoiodous acid, which promotes the cleavage of Se–Se bond in diselenide. The in situ generated active electrophilic selenium species then reacts with N,N-disubstituted aniline, affording 4-arylselanyl aniline with high regioselectivity and good yield via an electrophilic substitution. This metal-free catalytic method is convenient in neutral condition at room temperature and in short time, not only arylselanyl anilines, but also alkaylselanyl anilines have been prepared, which extends the catalytic application of KI in organic synthesis.
Keywords: arylselanyl aniline; diselenides; KI; electrophilic substitution; catalysis